(untitled) (Fiep Bulletin - online, 2013)
This study aims at analyzing the representation and the level of knowledge of three social groups on organ donation, transplants law and themes that raise ethical issues. The sample consisted of 25 students of the seventh level in the course in medicine at UFPB, 25 students in the 3rd year of the course of Law at UFPB and a group of 25 evangelizing people, of the fishermen´s villa in Manaíra, in the City of João Pessoa-Paraíba. The research was accomplished from December 2006 to February 2007. For the data collection, a questionnaire was used as instrument, consisting of open and closed questions. For the closed answers the descriptive statistical analyses were applied and for the justifications, the technique of content analysis was applied. The data has revealed that most of the interviewees is in favor of the donation of the organs, after the encephalic death, even as in life, except for the students of medicine that would only donate in life for relatives or friends. On the knowledge of the law of organ transplants, the data point that most does not know the law, and does not trust in the only list of beneficiaries. As for trusting in the diagnose of the encephalic death, 64% of the medicine students answered that they trust the diagnosis, while the students of Law and the fishermen´s villa, 40% and 48% answered that they do not know. Most of the informants answered that there is a preference for the organ trade, which is a possibility for anybody capable and judicially authorized to be an organ donor in life. It is concluded that there is a strong tendency for organ donation after an encephalic death and also in life, in the three groups, as well as deficiency in the knowledge on the organs donation and a certain distrust in the public section.